THE ROLE OF FAMILY TYPE AS DETERMINANT AND PREVALENCE OF TEENAGE PREGNANCY IN ORIADE LOCAL GOVERNMENT AREA OF OSUN STATE NIGERIA - Igaba Grace Onongha; Yejide Olulani Alebiosu; Moromoke Nimota Raji (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2023)
The study was designed to examine family type as determinant and prevalence of teenage pregnancy in Oriade Local Government Area (LGA) of Osun State, Nigeria. The study adopted the descriptive survey design of ex-post facto type. The study objectives included, to: ascertain family type as determinant of teenage pregnancy, examine the role of age in teenage pregnancy, and determine the influence of elder sibling(s) pregnancy on younger sibling(s) teenage pregnancy. A valid and reliable instrument; family type and pregnancy questionnaire (FT2PQ) was used to provide data for the study. The multi-stage selection procedure was adopted. Twenty towns were randomly selected from the LGA, with Family type as stratum. Housing units were further selected to participate in the study. Fifteen pregnant teenagers (identified in prior visits) were selected from each town using stratified sampling technique. In all, three hundred teenagers (100 from intact families, 100 from single parent families and 100 from step families) constituted the study sample. Data were analysed with Chi-square and Bivariate regression statistical methods. The results indicated that: family type was not a significant determinant of teenage pregnancy (x2=4.568, p˃0.206); age was not a significant determinant of teenage pregnancy (x2=2.333, p˃0.206); elder siblings’ pregnancy is responsible for 8.4% of the variation in younger siblings’ pregnancy. Based on the findings, recommendations included that parents communicate acceptable sexual values and attitude; ensure early sex education and guidance for older teenagers as a model for younger siblings